La experiencia sustituida: Hacia la construcción tecnológica de la nostalgia (2013)
This essay reflects on the relationship between technology and experience based on Walter Benjamin (and several theoretical updates), who addresses the matter in an ambivalent way: simultaneous possibilities and risks. From there, a number of questions are raised concerning the aura, authenticity, memory and technological construction of nostalgia through the simulation of imperfections in the image, blur and grain of film, among other possibilities. The final assessment of such a practice is ambivalent: both the reflective possibilities in the construction of an autobiographic tale as well as the impossibility of recounting history (political, social, and cultural) by substituting it with simulations of the past (the nostalgic image that has the power to romanticize the infamy of the present).